Winery website analysis framework: The case study of Srem wineries - Ćamilović Dragana (Turističko Poslovanje, 2022)
The purpose of this paper is to develop a framework that would enable analysis of wineries' websites from several aspects: Website Functionality, Interactivity, Visual Appearance, Contact Information, Winery Specific Information, Wine Tourism Related Services, and Online Shopping. The framework is then applied to analyse the Srem wineries' websites. The author has specifically chosen the Srem region because Srem's viticulture has a long tradition, and the wines produced there are of high quality. To be recognized as such in the world and to make Srem region interesting to wine consumers and wine tourists from various countries, the Srem wineries need to have a strong online presence, particularly in the form of websites. Unfortunately, the research presented in this paper reveals that a large number of Srem wineries do not have a website. The existing websites were studied in detail in accordance with the proposed framework. The project has its practical implications, since the framework presented can be of great help to wine business practitioners in understanding which features characterize a high-quality winery website.